Sistem Pendukung Keputusan Pemberian Insentif Kepada Karyawan Menggunakan Metode SMART - Lubis, Nisfu Sanna (CV. Graha Mitra Edukasi, 2024)
Providing employee incentives is a bonus given by the company to its employees, and is income outside of wages or salaries received every month. Giving incentives to employees at PT Gintar Pratama is done manually. However, the process of providing incentives to employees of PT Gintar Pratama is often not on target due to frequent miscalculations. This research was made to focus on these problems. The solution to the problem above is that the authors design a decision support system that can assist in solving the problem of giving incentives to employees of PT Gintar Pratama by using the SMART method in determining the weight of criteria and conducting rankings. This research produces a decision support system that can recommend giving incentives to PT Gintar Pratama employees use the SMART method. The results of this study are the creation of a decision support system for providing PT Gintar Pratama employee incentives using the SMART method. The method used is expected to create a very useful system, as well as a very accurate system. With the existence of a decision support system can provide recommendations to determine employees who are entitled to receive incentives.